P-42 Injectable medication at the end of life: a common task for generalist community clinicians. (1st March 2017) - Marvin, Rosamund; Grove, Sarah; Spathis, Anna; Barclay, Stephen
Abstract : Background: Injectable medications are commonly prescribed for patients at home approaching the end of their lives, either in response to, or in anticipation of, symptoms. Aims: With regard to injectable drugs for patients approaching the end of their lives in the community, to investigate: What drugs are prescribed? What drugs are administered? Who administers the drugs? Design and setting: Service evaluation of the Bedfordshire PEPS (Partnership for Excellence in Palliative Support) Co-ordination Centre, a 24 hour support service for palliative care patients. Medication data were extracted from patient records on SystmOne, the local community computerised healthcare record, concerning patients registered with PEPS who had died within a one year period. Results: Of 1087 patients registered with PEPS who died within a 1 year period, 392 (36%) were prescribed injectable medications, most commonly midazolam (88%), diamorphine (85%), cyclizine (72%) and glycopyrronium (67%). 328 (84%) out of the 392 spent part or all of their last week of life at home. Of these, 232 (71%) had injectable drugs administered during that time: diamorphine (72%), midazolam (66%), glycopyrronium (41%) and cyclizine (31%). Most (81%) were given more than one drug and half (52%) were given drugs both by continuous subcutaneous infusion and as stat doses. The drugs were most often given by generalist community nurses or nursing home staff (91%). There was little difference between drug prescription and administration in malignant or non-malignant disease. Conclusions: When prescribe, injectable medication is frequently used in the last week of life, especially diamorphine, midazolam, cyclizine and glycopyrronium. Administration is usually by staff who are not specialist in palliative care, highlighting the need for support and education for community healthcare professionals.